CHRONIC PAIN AS ONE OF THE FACTORS INFLUENCING THE DEVELOPMENT OF DEPRESSION - Sama, Ahmadova (Health and Society, 2024)
The article focuses on the investigation of chronic pain as a contributing factor to the development of depression in individuals experiencing chronic pain. The study discusses chronic pain and depression, exploring the connection between the two. Chronic pain is defined as pain that persists for more than 3 months and consistently manifests. Depression, on the other hand, is characterized by depressive symptoms lasting for a minimum of 2 weeks. To identify the link between chronic pain and depression, individuals with chronic pain were included in the study and the role of chronic pain in contributing to depression was examined. The results indicated that for the majority of patients with chronic pain, this pain plays a significant role in the onset of depression. Tests conducted on patients with chronic pain revealed moderate to high levels of depression. The findings demonstrate that chronic pain indeed plays a substantial role in the development of depression.